Państwowe osoby prawne (na tle zmian ustawowych po 1980 roku). - Jakubek, Marek (Wydział Prawa i Administracji UAM, 1988)
The article discusses different types of legal persons created by the State by virtue of statutes adopted after 1980. The author, referring to the distinctions accepted in the science of administrative law, distinguishes: 1) State legal persons of the "enterprise" type, among which — besides enterprises founded on the basis of the Act of Sept. 25, 1981 on State Enterprises — he includes State banks, post offices, State insurance companies, "Lot" and "Airports" enterprises, and research, artistic and film institutions; 2) State legal persons of the "public institution" type — schools of academic rank and the Polish Academy of Sciences; 3) organizational units of power engineering and mining industry and the Fund of Structural Changes in Industry as organizations of a specific character. Contrary to former views, the institution of a "legal person" proves to be useful in organizing diversified activity of the State. State legal persons differ in their structure and rules of activity with respect to both State organs and institutions as well as other subjects of private law.
State legal persons (in the light of statutory amendments after 1980)